Facing Competition: Educational Marketing Strategy at Madinah Karyatani Modern Islamic Boarding School / Menghadapi Persaingan: Strategi Pemasaran Pendidikan di Pondok Modern Madinah Karyatani - Dermawan, Oki; Rahmawati, Susi; Defriyanto, Defriyanto; Busmayaril, Busmayaril (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2024)
Madinah Karyatani Modern Islamic Boarding School, a modern Islamic boarding school, is currently facing intensified competition from other educational institutions. This necessitates the adoption of effective educational marketing strategies to maintain and enhance its competitive position in the educational market. This study investigates the marketing strategies employed by Madinah Karyatani Modern Islamic Boarding School to promote its educational services. A qualitative research approach, utilizing in-depth interviews and observations with key informants, such as management, teaching staff, and students, was employed. The findings highlight the strategic use of Arabic and English in promotional materials, partnerships with other educational institutions, and the utilization of social media to attract prospective students from diverse regions. These strategies indicate a shift in the institution’s approach to education in response to a growing demand for value-based education in a globalized context. The novelty of this research lies in its exploration of modern marketing strategies in Islamic education and provides insights into responsive strategy development that addresses the dynamics of the educational market.